2021
DOI: 10.18019/1028-4427-2021-27-6-727-731
|View full text |Cite
|
Sign up to set email alerts
|

The problem of adipose degeneration of the paraspinal muscles in patients after surgery for degenerative stenosis

Abstract: Degeneration of the multifidus muscle of the back after stabilizing operations on the lumbar spine and its impact on rehabilitation measures remains understudied. There are isolated data in publications on the partial effectiveness of minimally invasive surgery, but the problem has not been completely solved, there is no data on the effect of physical therapy and physiotherapy methods on the progress of degeneration of the multifidus muscle of the back. Purpose To study the effect of electroneuromyostimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In Part I (5-14 days after surgical intervention): light warm-up (10 min); knee extension while lying supine with the spine in a neutral position and the hip flexed to a 90° angle ( Russian physicians & sport professionals presented information about the possibility of successful rehabilitation of professional athletes after operative treatment of LDH, with helping of 8-weeks electroneuromyostimulation therapy with simultaneous restriction of motor activity for involve decrease of stress forces at the back [29]. Also, physicians reported that combination of early postoperative stimulation (electroneuromyostimulation) and restriction of motor activity for 2 months with a subsequent transition to physical therapy is optimal for patients with operative treatment of lumbar spine [30]. Physicians reported on the high efficiency of the course of electroneuromyostimulation therapy for patients with back pain, including LBP and LDH [13,15,29,31].…”
Section: Methodsmentioning
confidence: 99%
“…In Part I (5-14 days after surgical intervention): light warm-up (10 min); knee extension while lying supine with the spine in a neutral position and the hip flexed to a 90° angle ( Russian physicians & sport professionals presented information about the possibility of successful rehabilitation of professional athletes after operative treatment of LDH, with helping of 8-weeks electroneuromyostimulation therapy with simultaneous restriction of motor activity for involve decrease of stress forces at the back [29]. Also, physicians reported that combination of early postoperative stimulation (electroneuromyostimulation) and restriction of motor activity for 2 months with a subsequent transition to physical therapy is optimal for patients with operative treatment of lumbar spine [30]. Physicians reported on the high efficiency of the course of electroneuromyostimulation therapy for patients with back pain, including LBP and LDH [13,15,29,31].…”
Section: Methodsmentioning
confidence: 99%